Divorcees. Tolerance to two (Journal of Parents and Teachers, 1995)
The author reflects on the complexity of interpersonal relationships, suggesting that sometimes it is better to sever the relationship if it becomes untenable. He concludes that it is easier to manage a separate relationship than a complicated one.
Keywords: relationships; complexity; sustainable; separation